Implementation of Electronic Customer Relationship Management on the Instagram Platform: Case Study on MSMEs Perfume Products - Simatupang, Frido Sarita; Rahayu, Agus; Hendrayati, Heny (Research Collaboration Community (Rescollacom), 2024)
Micro, Small and Medium Enterprise High Romantic Mens (HRM) Perfume was founded in 2019. This Micro, Small and Medium Enterprise operates in the fashion sector which operates in the online marketing sector in terms of marketing and the Micro, Small and Medium Enterprise has 30 reseller members. This research aims to determine the application of Electronic Customer Relationship Management (E-CRM) on the Instagram platform and determine the efforts made to improve good service, quality products and fast delivery in Micro, Small and Medium Enterprises using descriptive research methods. The research results show that the implementation of electronic customers relationship management on the Instagram platform is good and the service to consumers is quite good, a good image on Instagram still needs to be improved again by carrying out paid promotions and endorsements. The parties need to be aware of this condition. Micro, Small and Medium Enterprises to increase transaction potential so that the goals of Micro, Small and Medium Enterprises will be achieved.